Network technology research under cloud computing environment - Lei XU; Yun-yong ZHANG; Jun WU; Bing-yi FANG (Tongxin xuebao)
The framework of cloud computing network around data center was proposed.Through the analysis of new demands of the network in the cloud computing environment,new technologies were discussed in detail for the virtual machine local network,data center local network,across data center network,user access network and SDN.Development proposal was provided in order to prepare for the implementation of cloud computing network technology.